2020
DOI: 10.3390/ijms21218037
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Implementation for HIC Retention Time Prediction of mAbs Using Fab Structure: A Comparison between Structural Representations

Abstract: Monoclonal antibodies (mAbs) constitute a rapidly growing biopharmaceutical sector. However, their growth is impeded by high failure rates originating from failed clinical trials and developability issues in process development. There is, therefore, a growing need for better in silico tools to aid in risk assessment of mAb candidates to promote early-stage screening of potentially problematic mAb candidates. In this study, a quantitative structure–activity relationship (QSAR) modelling workflow was designed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Increase in the availability of monoclonal antibody (mAb) experimental characterizations, access to accurate structural information, and homology modeling (HM) capabilities have fostered the development of computational approaches to address several developability aspects of biotherapeutics . In silico evaluations do not require any material and can be performed either in parallel to or ahead of the experimental evaluations to support drug discovery, as shown by several works describing the prediction of experimental properties. However, these tools often tackle individual aspects of developability and do not take into consideration that the optimization of one antibody feature may potentially have detrimental effects on other properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in the availability of monoclonal antibody (mAb) experimental characterizations, access to accurate structural information, and homology modeling (HM) capabilities have fostered the development of computational approaches to address several developability aspects of biotherapeutics . In silico evaluations do not require any material and can be performed either in parallel to or ahead of the experimental evaluations to support drug discovery, as shown by several works describing the prediction of experimental properties. However, these tools often tackle individual aspects of developability and do not take into consideration that the optimization of one antibody feature may potentially have detrimental effects on other properties.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a single static-energy-minimized antibody conformation is therefore a simplification of a complex conformational landscape that responds to the changes in the environmental conditions of the antibody molecule as it passes through various stages of formulation, manufacturing, and in vivo administration. Moreover, homology models generated using crystal structure templates may keep imprints from the template, suffer from crystal packing effects, and not accurately represent the dominant conformation of the antibody in solution. , For these reasons, it is desirable that in silico methods include, wherever feasible, conformational ensembles accessible to the antibody candidates. , …”
Section: Introductionmentioning
confidence: 99%
“…A range of established multivariate data analysis (MVDA) techniques can be valuable for this purpose, as proposed in [18]. Advances in molecular dynamics (MD) modelling also offer an exciting opportunity to increase the understanding of the viral particle behaviour during manufacturing, akin to the benefits such an approach offers in monoclonal antibody (mAb) early process development and manufacturability assessment [51]. Karlberg et al [51] demonstrated that MD can be used effectively for in silico early-stage screening of potentially problematic mAb candidates.…”
Section: Perspectives and Implementation Challengesmentioning
confidence: 99%
“…Advances in molecular dynamics (MD) modelling also offer an exciting opportunity to increase the understanding of the viral particle behaviour during manufacturing, akin to the benefits such an approach offers in monoclonal antibody (mAb) early process development and manufacturability assessment [51]. Karlberg et al [51] demonstrated that MD can be used effectively for in silico early-stage screening of potentially problematic mAb candidates. An approach similar to their proposed quantitative structure-activity relationship (QSAR) modelling workflow for the prediction of hydrophobic interaction chromatography (HIC) retention times of mAbs can be envisaged for in silico exploration of viral particle behaviour during processing or transduction.…”
Section: Perspectives and Implementation Challengesmentioning
confidence: 99%
“…Quantitative structure-property relationships (QSPR) leverage machine learning algorithms and existing data to predict a target property based on the protein structure. When process understanding and experimental data is limited, QSPR models give initial insights into the developability of mAb candidates during early-stage development (Karlberg et al, 2020(Karlberg et al, , 2018. Kizhedath et al (2019) developed a QSPR model for the prediction of retention times in cross-interaction chromatography that revealed the relevance of local protein descriptors on protein-protein interactions.…”
Section: Introductionmentioning
confidence: 99%